24 Reputation

6 Badges

16 years, 82 days

MaplePrimes Activity

These are Posts that have been published by griffgruff

The function pdsolve gives different answers depending upon the way the problem is posed. For example:

> PDE1:=a*diff(u(x,t),t)+b*diff(u(x,t),x)-u(x,t)^2=0;
> ans1:=pdsolve(PDE1);


> ans1 := u(x,t) = b/(-x+_F1(-(-t*b+a*x)/b)*b);


> PDE2:=a*diff(u(t,x),t)+b*diff(u(t,x),x)-u(t,x)^2=0;
> ans2:=pdsolve(PDE2);

which is the same problem but with u(x,t) replaced by u(t,x), gives:

> ans2 := u(t,x) = a/(-t+_F1((-t*b+a*x)/a)*a);

Both are actually correct solutions, as is easily verified by a call to pdetest.

My query is:
Page 1 of 1